Plausible impact of forward head posture on upper cervical spine stability - Chu, Eric C. P. (J Family Med Prim Care, 2020)
The cervical spine is responsible for allowing mobility and stability to the head and neck. Any deviation to the center of gravity of the head results in an increase in cantilever loads, which can be particularly damaging to the upper cervical joints. Excessive neck bending also exaggerates stretching through the cervical spine and all of the spinal structures below. It has been reported that forward head posture (FHP) can cause a multitude of disorders including cervical radiculopathy, cervicogenic headaches and cervicogenic dizziness. Most of these conditions manifest with clusters of painful symptoms and spine dysfunctions. The purpose of this case study is to describe the radiographic imaging considerations and to illustrate the potential impacts in symptomatic adults with FHP. We randomly selected radiographs of three individuals with FHP who had undergone cervical adjustment for cervical pain. The occipito-axial (C0-C2) and atlanto-axial (C1-C2) joints were assessed via the C0-2 distance from the C2 base to the McGregor line (Redlund-Johnell criterion) and the Ranawat C1-2 index, in addition to subjective radiographic parameters. By comparing the radiographs of before-and-after intervention of each patient, a regressive joint spacing was observed from both indices. Such a long-lasting stretching concordant with FHP was assumed to be hazardous to joint stability. A definite conclusion, however, cannot be drawn due to the small sample size and a lack of convincing measurements.